Teach Yourself VISUALLY iPhone 16 - Hart-Davis, Guy (John Wiley & Sons, Incorporated, 2025)
Teach yourself VISUALLY ™ Are you a visual learner? Do you prefer instructions that show you how to do something--and skip the long-winded explanations? If so, then this book is for you. Open it up and you'll find clear, step-by-step screen shots that show you how to tackle more than 120 iPhone tasks. Each task-based spread covers a single technique to help you master any iPhone 16 model and iOS 18 in no time. You'll learn to: Set up and activate your iPhone Customize iOS to work your way Chat via Messages, Phone, and FaceTime Use Apple Intelligence AI tools Shoot pro-quality photos and videos Designed for visual learners Two-page lessons break big topics into bite-sized modules Succinct explanations walk you through step by step Full-color screen shots demonstrate each task Helpful sidebars offer practical tips and tricks.
Description based upon print version of record
Keywords: iPhone (Smartphone); Smartphones; Mobile computing; iPhone (Téléphone intelligent); Téléphones intelligents; Informatique mobile